PENGARUH BID-ASK SPREAD, MARKET VALUE, KEBIJAKAN DIVIDEN, DAN VOLUME PERDAGANGAN TERHADAP HOLDING PERIOD - Wildayani, Wila; Wiharno, Herma; Nurfatimah, Siti Nuke; Fitriani, Chintia (Program Studi Akuntansi, Universitas Kuningan, 2023)
The purpose of this study is to examine and analyze the effect of Bid-Ask Spread, Market Value, Dividend Policy, and Trading Volume on the Holding Period of Tourism & Recreation Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Sample selection using quota sampling technique and samples that meet the criteria of 29 companies. Data collection techniques were carried out using non-participant observation methods. The research method used is descriptive verifiative. The hypothesis was tested using panel data regression analysis technique with E-Views per 9.0. The model selection test in research is a fixed effect model. The results of the study are known that bid-ask spread has a significant positive effect on the holding period, market value has a significant positive effect on the holding period, Dividend policy with dividend payout ratio indicator has a significant positive effect on the holding period, and trading volume has a significant negative effect on the holding periodKeywords : Holding Period, Bid-Ask Spread, Market Value, Dividend Policy, Trading Volume